2008
DOI: 10.1529/biophysj.107.127951
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanism of ADP Action on Flagellar Motility Derived from Studies on Bull Sperm

Abstract: Adenosine diphosphate (ADP) is known to have interesting effects on flagellar motility. Permeabilized and reactivated bull sperm exhibit a marked reduction in beating frequency and a greatly increased beat amplitude in the presence of 1-4 mM ADP. In this study we examined the force production of sperm reactivated with 0.1 mM ATP with and without 1 mM ADP and found that there is little or no resulting change in the stalling force produced by a bull sperm flagella in response to ADP. Because bull sperm bend to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 41 publications
4
54
1
Order By: Relevance
“…We have demonstrated that reactivated, de-membranated bull sperm show a significant increase in the t-force at the switch-point of the beat in the presence of ADP (Lesich et al, 2008). This is in agreement with experimental studies on the nucleotide regulation of dynein, which assert that the binding affinity of dynein for tubulin is directly regulated through a long-residence ADP-binding site on the dynein head (Inoue and Shingyoji, 2007;Cho et al, 2008).…”
Section: Nucleotide Regulation Of Dyneinsupporting
confidence: 89%
See 1 more Smart Citation
“…We have demonstrated that reactivated, de-membranated bull sperm show a significant increase in the t-force at the switch-point of the beat in the presence of ADP (Lesich et al, 2008). This is in agreement with experimental studies on the nucleotide regulation of dynein, which assert that the binding affinity of dynein for tubulin is directly regulated through a long-residence ADP-binding site on the dynein head (Inoue and Shingyoji, 2007;Cho et al, 2008).…”
Section: Nucleotide Regulation Of Dyneinsupporting
confidence: 89%
“…The dynein illustration is based on the proposal put forth by Inoue and Shingyoji (Inoue and Shingyoji, 2007). Figure adapted from Lesich et al (Lesich et al, 2008).…”
Section: Nucleotide Regulation Of Dyneinmentioning
confidence: 99%
“…Its stiffness ranges from 15 3 10 221 N • m 2 in bull sperm (Lesich et al, 2008) to 300 3 10 221 N • m 2 in rat sperm (Lindemann et al, 2005) with mouse sperm being intermediary (data not published). This compares to a value of 1 3 10 221 N • m 2 in sea urchin (Pelle et al, 2009) The torque required to bend a flagellum is the product of the curvature multiplied by the stiffness.…”
Section: Consequences Of Anatomy On Motilitymentioning
confidence: 99%
“…This induced infertility could potentially be of value as a male contraceptive. It has the advantages that it would be reversible, and because the calcineurin involved is sperm specific, it could conceivably be targeted by inhibitors selective for the sperm calcineurin.When we measured the stiffness of bull sperm and rat sperm we found great variability from cell to cell (SchmitzLesich and Lindemann, 2004;Lindemann et al, 2005;Lesich et al, 2008). The variability was always most pronounced in the midpiece, the stiffest portion of the flagellum.…”
mentioning
confidence: 99%
See 1 more Smart Citation